2011
DOI: 10.1016/j.jvs.2010.12.070
|View full text |Cite
|
Sign up to set email alerts
|

A link between smooth muscle cell death and extracellular matrix degradation during vascular atrophy

Abstract: Objective We have previously reported that high blood flow induces neo-intimal atrophy in polytetrafluoroethylene (PTFE) aorto-iliac grafts and that a tight external PTFE wrap of the iliac artery induces medial atrophy. In both non-human primate models, atrophy with loss of smooth muscle cells and extracellular matrix (ECM) begins within 4 days. We hypothesize that matrix loss is linked to cell death, but the factors and mechanisms involved are not known. The purpose of this study was to determine commonly reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Loss of aortic wall SMCs via apoptosis may also contribute to aneurysm development through other mechanisms. 23 Given that SMCs represent the major source of ECM protein production, apoptosis of SMCs may reduce the ability to repair connective tissue loss during early vessel wall remodeling and development. 24 Indeed, our laboratory has previously reported that reduced elastogenesis coincides with increased apoptosis during early aneurysm development in this model system.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of aortic wall SMCs via apoptosis may also contribute to aneurysm development through other mechanisms. 23 Given that SMCs represent the major source of ECM protein production, apoptosis of SMCs may reduce the ability to repair connective tissue loss during early vessel wall remodeling and development. 24 Indeed, our laboratory has previously reported that reduced elastogenesis coincides with increased apoptosis during early aneurysm development in this model system.…”
Section: Discussionmentioning
confidence: 99%
“…The fragments generated by the ADAMTS enzymes and other proteases have also been observed to build up in lesions in both human [92] and in several different animal models of vascular disease [93, 98, 103]. In fact, in a primate model of blood flow-induced intimal atrophy, Kenagy and colleagues found a selective increase in ADAMTS4 and fragmented versican coinciding with ASMC death and lesion regression [93, 103-106]. Furthermore, this group went on to show that Fas ligand induced ADAMTS4 synthesis by ASMCs in vitro and that ADAMTS4 colocalized with TUNEL-positive SMCs in the vascular graft [93, 103].…”
Section: Chondroitin Sulfate Proteoglycans (Cspgs)mentioning
confidence: 99%
“…Furthermore, this group went on to show that Fas ligand induced ADAMTS4 synthesis by ASMCs in vitro and that ADAMTS4 colocalized with TUNEL-positive SMCs in the vascular graft [93, 103]. In an extension of these studies, Kenagy and colleagues compared the neointimal atrophy that occurs in the baboon model of vascular graft failure to a tight external wrap graft failure model and found that of 23,000 genes, only three ECM-modifying genes were common to both models with ADAMTS4 being one of them [106]. Such findings implicate this enzyme and versican turnover as important players in vascular disease.…”
Section: Chondroitin Sulfate Proteoglycans (Cspgs)mentioning
confidence: 99%
“…ADAMTS-1 and ADAMTS-4 were found to be highly expressed in macrophage-rich areas of human atherosclerotic plaque [11,12]. In addition, ADAMTS-4 was shown to be associated with VSMC death and vascular atrophy, and an ADAMTS-1 gene variation was shown to be associated with an increased risk of coronary artery disease events [13,14]. Most notably, Taketani and colleagues reported that ADAMTS1 expression was significantly upregulated in TAA patients in DNA microarray and real-time PCR experiments [10].…”
Section: Commentmentioning
confidence: 99%